Peningkatan Hasil Pembelajaran Sains melalui Permainan Tabung Teka-teki pada Kelompok B2 di Taman Kanak-kanak Negeri Pembina Lima Puluh Kota - Yusni, Deli (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2019)
This research was motivated by a lack of interest in Group B2 children in TK Negeri Pembina Lima Puluh Kota Kecamatan Harau in participating science learning about the five senses so that there was a need for improvement. The purpose of this Classroom Action Research is to describe the improvement in the results of science learning about the five senses in the TK Negeri Pembina Lima Puluh Kota. The type of the research carried out was classroom action research with the subject of research of students in the TK Negeri Pembina Lima Puluh Kota in Group B2, which were consisted of 15 pupils using the Puzzle Tube Educational Tool. The technique used in collecting data in the form of observation, and the format of the results of interviews, test, then processed by percentage techniques. This classroom action research was conducted in two cycles. The results of the study in the first cycle of improvement in learning outcomes have not reached 75%, then continued in the second cycle where the increase in children's learning outcomes becomes more increasing. So the results of the average rate of children exceed the minimum completeness criteria that have been set. Thus it can be concluded that the efforts of researchers to improve children's learning outcomes in learning science about the senses. After the actions taken from cycle I and cycle II can be achieved.